2014
DOI: 10.18380/szie.colum.2014.1.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the antifungal potential of the essential oil from Thymus vulgaris against Botrytis cinerea causative agent of postharvest grey mould on strawberry fruits

Abstract: Depending on commodity and region, postharvest diseases can cause considerable economic losses. Although effective against postharvest pathogens, synthetic pesticides have gained increasingly negative attention over the past years from the public opinion. Among natural fungicides, plant derived compounds such as essential oils (EOs), have become topic of increasing discussion over the last couple of decades as safe and ecologically friendly alternatives to synthetic pesticides. Grey mould caused by Botrytis ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…After 15 days of storage, results showed that thyme EO at 10% was statistically beneficial against P. expansum, and treatments with 1% and 10% of the EO were statistically similar to the chemical control for B. cinerea [55]. Gebel and Magurno [78] investigated the in vivo antifungal activity of T. vulgaris essential oil at two concentrations: 200 µL/mL and 500 µL/mL. They demonstrated a high efficacy of thyme EO in reducing gray mold incidence and found that a 500 µL/mL dose effectively inhibited B. cinerea mycelial growth after 7 days.…”
Section: Discussionmentioning
confidence: 87%
“…After 15 days of storage, results showed that thyme EO at 10% was statistically beneficial against P. expansum, and treatments with 1% and 10% of the EO were statistically similar to the chemical control for B. cinerea [55]. Gebel and Magurno [78] investigated the in vivo antifungal activity of T. vulgaris essential oil at two concentrations: 200 µL/mL and 500 µL/mL. They demonstrated a high efficacy of thyme EO in reducing gray mold incidence and found that a 500 µL/mL dose effectively inhibited B. cinerea mycelial growth after 7 days.…”
Section: Discussionmentioning
confidence: 87%
“…Nabigol and Morshedi (2011) found that TEO delayed the onset of gray mold symptoms in tomatoes and strawberries. Similarly, Gebel and Magurno (2014) observed that gray mold symptoms in untreated strawberries began to appear 3 days after inoculation, whereas in strawberries treated with TEO appeared on day 5. Some authors agree that the mechanism by which TEO decreases the growth of microorganisms is due to the hydrophobicity of their compounds, which allows them to interact with the lipids of the fungal cell membrane.…”
Section: Resultsmentioning
confidence: 72%
“…Já para Carvalho et al (2009) Nos últimos anos, muitos trabalhos têm relatado o potencial de óleos essenciais e extratos de plantas medicinais como alternativa no controle de doenças pós-colheita (ALMEIDA et al, 2009;BRAGA, 2012;DEMARTELAERE et al, 2015;GEBEL;MAGURNO, 2014;MOURA et al, 2012;SAUTTER et al, 2011) …”
Section: Introductionunclassified